2018
DOI: 10.1016/j.drugalcdep.2018.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Informing drinkers: Can current UK alcohol labels be improved?

Abstract: HighlightsDrinkers underestimated the number of drinks that constituted 14 units.Unit understanding was greater for novel unit labels compared to industry labels.Motivation to drink less was higher for cancer and negatively-framed messages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 24 publications
6
59
0
1
Order By: Relevance
“…Targeted messaging for different groups is also supported by the importance of personal relevance which in our logistic regression had the highest adjusted odds ratio for all seven labels. Our analyses confirm that the determinants of a positive responses to health label are complex and that in some cases personal relevance (and believability) of the messages are more important predictors of the message effectiveness than individual differences (Blackwell et al, 2018;Pettigrew et al, 2016).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Targeted messaging for different groups is also supported by the importance of personal relevance which in our logistic regression had the highest adjusted odds ratio for all seven labels. Our analyses confirm that the determinants of a positive responses to health label are complex and that in some cases personal relevance (and believability) of the messages are more important predictors of the message effectiveness than individual differences (Blackwell et al, 2018;Pettigrew et al, 2016).…”
Section: Discussionsupporting
confidence: 63%
“…While our analysis of global drinkers support the use of cancer messages that are positively framed (drinking less reduces your risk), it is likely that there are differences across cultures. For example while an Australian study found that positive frames appeared to be more effective, a UK sample found negatively framed messages to be more effective (Blackwell et al, 2018). Future research should assess these potential regional differences.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As shown in Figure 1, the alcohol labelling intervention consisted of three rotating labels: (1) a cancer warning including specific references to breast and colon cancers-two prevalent, often fatal cancers in Canada [48], (2) Canada's low-risk drinking guidelines, and (3) standard drink information (four separate labels were developed for wine, spirits, coolers, and beer). Consistent with previous studies examining effective product label design, the intervention labels were relatively large in size to make them easily noticed and read, were full colour with a bright yellow background and red border so that they stand out on the container, and had messages providing new information and were rotated to avoid wear out [41,47,[49][50][51][52][53][54][55]. A recent evaluation of the label intervention conducted by Hobin et al, on which the analyses of this paper are also based, found that participant knowledge of the link between alcohol and cancer was approximately 25% before the alcohol labelling intervention [56].…”
Section: Introductionmentioning
confidence: 87%
“…Incrementando el tamaño y usando un semáforo nutricional, las etiquetas del volumen de alcohol serían capaces de atraer mayores niveles de atención. Investigaciones previas apoyan estos resultados (Blackwell et al, 2018;Farke, 2011;Graham et al, 2012;Kersbergen y Field, 2017). En España, como en la mayoría de los países europeos, las bebidas alcohólicas no están obligadas a incluir advertencias sanitarias acerca de los riesgos del consumo de alcohol (Farke, 2011), a pesar de su potencial para comunicar los perjuicios asociados al consumo de alcohol y para disuadir patrones de consumo de riesgo entre los consumidores (Blackwell et al, 2018).…”
Section: Discussionunclassified